Inappropriate Transfer of Burn Patients: A 5-Year Retrospective at a Single Center. Issue 1 (January 2021) - Slavin, Benjamin; Shoucair, Sami; Klifto, Kevin; Grzelak, Michael; Shetty, Pragna; Cox, Carrie; Javia, Vidhi; Asif, Mohammed; Hultman, C. Scott
Abstract : Objective: Burn injuries have an annual incidence exceeding 40, 000. The Burn Center Referral Criteria published by the American Burn Association (ABA) serve to guide health centers in determining appropriateness of patient transfer to a specialized center. With inappropriate transfer rates reaching up to 77%, reliance on the ABA criteria is critical as the decision to transfer a patient can impose significant costs to both the patient and healthcare system. The aim of this study is to evaluate the appropriateness of all burn patient transfers to a single burn center over a 5-year period and assess the potential role of telemedicine to optimize the assessment and care of this patient population. Methods: A 5-year retrospective review was conducted to all burn patients transferred or consulted for transfer to our burn center between January 2013 and January 2017. After application of inclusion and exclusion criteria, 767 cases were analyzed, with 612 ultimately being transferred. Outcome measures included basic clinical and demographic information, as well as logistical burn and transfer data such as percent total body surface area and transfer distance. After data collection, 5-year descriptive trends were analyzed, and the ABA criteria were applied to each patient case to evaluate appropriateness of transfer. Patients transferred despite not meeting at least one of the ABA criteria were classified as inappropriately transferred. Results: A total of 25 patients (3.2%) were found to be inappropriate transfers. Statistical analysis compared appropriately transferred patients (n = 587) with those inappropriately transferred. Overall, inappropriately transferred patients were more likely to have superficial partial thickness burns (76% vs 46%, P = 0.05), were less likely to need surgery (4% vs 22%, P < 0.05), and had a higher incidence of upper extremity burns (32% vs 4%, P < 0.01). Conclusions: Our study increases awareness of the most commonly seen presentation of inappropriately transferred burn patients over a 5-year period at our center. Given the advent of telemedicine, the ability of institutions to pinpoint a subset of patients most vulnerable to inappropriate transfer will allow for a streamlining of resources that will serve to benefit both patients and the health system.